2017
DOI: 10.1177/1350506817742929
|View full text |Cite
|
Sign up to set email alerts
|

Egg freezing experiences of women in Turkey: From the social context to the narratives of reproductive ageing and empowerment

Abstract: This article explores egg freezing experiences of women in Turkey. Since 2014, it has been legal in Turkey to use egg freezing technology for ageing women, while it was previously allowed only for disease-related purposes. In cooperation with a private fertility clinic in Istanbul, the authors conducted 21 interviews with older, single women who held either professional or managerial positions and who were undergoing or had undergone the procedure. Drawing on a qualitative analysis of these interviews, the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…This technology has been developed in a world characterized by increased female labor force participation, changing family structures, and economic liberalization (Esping-Andersen, 2015; Streeck, 2009). The increased flexibility of labor markets and the insufficiency of welfare state institutions concerning child and elderly care, among others, contribute to the postponement of motherhood and encourage women's decision to freeze eggs, as we show elsewhere (Göçmen and Kılıç, 2017; see also Cattapan et al, 2014).…”
Section: The Role Of Social Norms and Beliefsmentioning
confidence: 82%
“…This technology has been developed in a world characterized by increased female labor force participation, changing family structures, and economic liberalization (Esping-Andersen, 2015; Streeck, 2009). The increased flexibility of labor markets and the insufficiency of welfare state institutions concerning child and elderly care, among others, contribute to the postponement of motherhood and encourage women's decision to freeze eggs, as we show elsewhere (Göçmen and Kılıç, 2017; see also Cattapan et al, 2014).…”
Section: The Role Of Social Norms and Beliefsmentioning
confidence: 82%
“…This leads to feelings of frustration and misrecognition. In addition, many studies around the world have found that women’s decision to postpone motherhood is not exclusively a conscious decision but is based on variables beyond their control such as finding a committed partner [ 1 , 50 53 ]. This observation could support the hypothesis that these women are unfairly disadvantaged in the allocation of public resources.…”
Section: Discussionmentioning
confidence: 99%
“…5,[32][33][34][35][36][37]39,43,51,57,58 In 6 studies, the majority of women were characterized as full-time employed or just employed. 17,38,41,42,46,48,50 Eleven studies identified most participants as white. 32,34,35,39,41,42,45,48,[50][51][52][53]57 Most women were described as heterosexual [32][33][34][35]39,40,43,45,[50][51][52]57 and childless 5,44,47,48,50,56 at the time of egg freezing.…”
Section: Characteristics Of Users or Potential Users Of Planned Oocyt...mentioning
confidence: 99%